The Chronic Effect of Endurance Training On Jip3 Gene Expression in Soleus Muscle of Male Wistar Rats - Abdolreza Kazemi; Jamileh Kermani; Masoud Rahmati (Journal of Advanced Biomedical Sciences, 2016)
Background & Objective: Adaptations in neuromuscular system are due to changes in the expression and activity of proteins and its transmitters. JIP 3 protein plays a role in the regulation of structure and function of neurons as well as the establishment of multi-nuclear muscle cells. Considering the effects of exercise on neuromuscular system, the present study aimed to investigate the effects of 6 weeks of endurance training on JIP3 gene expression in soleus muscle of male Wistar rats.